Effect of antihistamine-containing syrup on salivary metabolites: an in vitro and in vivo study - Tatiana Kelly da Silva Fidalgo; Liana Bastos Freitas-Fernandes; Fabio Ceneviva Lacerda Almeida; Ivete Pomarico Ribeiro de Souza; Ana Paula Valente (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract This study tested the null hypothesis that antihistamine-containing syrup does not change salivary metabolites in vitro and in vivo. For the in vitro experiments, saliva from 10 volunteers was mixed with a syrup or pill suspension of loratadine (1 mg/ml Claritin®, Schering-Plough, Rio de Janeiro, Brazil). For the in vivo experiment, 10 volunteers performed a mouth rinse with 10 mL of antihistamine syrup (Claritin®; Schering-Plough, Rio de Janeiro, Brazil) for 20 seconds and then discarded the rinse water. After 20 seconds, 5 mL of unstimulated whole saliva was spit into a plastic tube kept on ice. The protein profile of in vitro and in vivo experiments was analyzed using 12% sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The samples were also analyzed by nuclear magnetic resonance (NMR) spectroscopy, followed by Principal Component Analysis and Wilcoxon test (p < 0.05). There were differences in salivary metabolites after syrup interaction. The salivary concentrations of acetate, n-caproate, arginine, glutamate, and lysine among other metabolites were reduced with the syrup in both in vivo and in vitro experiments (p < 0.05), but no differences were observed when the pill suspension was used (p > 0.05). Similar changes in metabolite profiles were observed in both in vitro and in vivo experiments. Electrophoresis revealed no difference in the salivary protein pattern. The null hypothesis was rejected because the intake of syrup medicine changes the salivary composition and influences oral homeostasis and susceptibility to oral diseases.